The Analysis of Arabic Learning Materials in Al-‘Arabiyah Baina Yadaik Book with the Principle of Material Development Approach - Muhammad Ediyani; Kasful Anwar; Husaini Husaini; Ridha Zuhaimi; Taufiq Hidayat (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the material in the book al-'Arabiyah Baina Yadaik by Dr. Abdurrahman bin Ibrahim AlFauzan, Dr. Mukhtar At-Thahir Hasin, and Dr. Muhammad Abdul Khaliq Muhammad Fadhli with the principle approach to the development of material and wants to reveal the advantages of material design. This research is a library research with al-’Arabiyah Baina Yadaik's research object. The study was conducted using the method of observing books that were observed both primary and secondary. Meanwhile, to analyze the data the researcher used content analysis techniques. The results of this study indicate that this book is feasible and appropriate to be used as teaching material in Arabic for non-Arabic speakers. the advantages of al-'Arabiyah Baina Yadaikyaitu's book (1) introducing modern theories in Arabic teaching (2) using easy and gradual methods (3) applying language skills: hearing, speech, reading, and writing (4) providing optional tests according to level (5) is supplemented with supporting materials that help the learning program (6) suitable for all levels (elementary, middle, tertiary) both young and old who want to quickly master Arabic. As for the shortcomings of this book, there is no interesting picture (visualization) that can foster its own motivation in studying the book.